Evaluation of Droplet Digital PCR Assay for the Diagnosis of Candidemia in Blood Samples - Chen, Biao; Xie, Yingguang; Zhang, Ning; Li, Wenqiang; Liu, Chen; Li, Dongmei; Bian, Shaodong; Jiang, Yufeng; Yang, Zhiya; Li, Renzhe; Feng, Yahui; Zhang, Xiaojie; et al. (Frontiers in Microbiology, 2021)
An increasing number of studies have shown that droplet digital PCR (ddPCR) is a promising tool for pathogen diagnosis, even samples with low concentration DNA. The aim of this study is to optimize and evaluate the diagnostic accuracy of ddPCR assay for candidemia for early diagnosis. We first designed and synthesized candida primers and probe and evaluated the sensitivity and specificity of ddPCR assay in vitro. Then we set up a mouse candidemia model to evaluate the capability of ddPCR for Candida DNA detection in blood samples of the infected mice. Finally, 45 blood samples from patients with suspected candidemia were tested with ddPCR assay. ddPCR assay has an almost ideal sensitivity and specificity, with detection capacity at 4.8 copies per reaction in candidemia samples and in vitro test. Meanwhile, the positive rate of detection, sensitivity, specificity, and positive and negative predictive values of ddPCR are significantly improved in comparison with culture and qPCR methods. This study demonstrates that ddPCR assay with high specific and sufficient sensitivity is a promising method for timely diagnosis, and monitor of treatment response by quantification of DNA in blood samples from candidemia.